Children’s Addiction to Video Games: Causes and Effects - asmani, rachida (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract : Technology is a double-edged sword, a blessing and a curse.. Many of us have heard this sentence at least once in their lives, yet many people see the good in technology much more than they see the bad in it, especially in children who do not know how negative it is in what it offers They have games, where for a short time the addiction starts from a simple dose, when the child gets acquainted at an early age with these games, then the matter develops, and he begins to spend more and more time immersed in them until eventually the matter reaches an extreme point, neglecting his studies , and even cut ties with their families completely, locking themselves in their rooms to be alone with their toys.